The graunding of vacuumthermal mechanism of moisture diffusion of capillary-porous bodies - Gaponjuk, Igor (My University, 2016)
Research of methods of power-handling of pressure is in-process executed in capillaries kapilyarno-poristikh bodies on powerhungryness of drying of these bodies. Can be drawn on results in scientific and practical spheres. В роботі виконано дослідження способів управління енергією тиску в капілярах капілярно-пористих тілах на енергоємність сушіння цих тіл. Результати можуть бути використані у науковій та практичній сферах.
Keywords: drying; grain; energy content; heat regeneration; drying apparatus; energy economy drying; сушіння; зерно; теплота; рекуперація теплоти; енерго-ощадне сушіння; кафедра технології зберігання і переробки зерна